The Social Power Ideology between Buddhist and Islam Represented in Times Magazine - Mirfa’un Nu’ma (Tebuireng: Journal of Islamic Studies and Society, 2022)
This study aimed to determine the critical discourse analysis of news about Rohingya refugees published by theTimes magazine.The qualitative descriptive method is used as the basis for thinking, and thecritical paradigm is used as the point of view of this analysis. The theoryused is the theory of Power and Domination from Teun Van Dijk. The subject of this research is a discourse leaked by the Times magazine entitled "When Buddhist Go Bad". The results of his research are that the Times Magazine represents the Buddhist doctrine in Myanmar with extreme social power and dominance because it is defended by the Myanmar state to discriminate against Rohingya refugees. Furthermore, as a result of the ideology, socialpower, and domination that the Buddhists own, in the result, the discrimination must be accepted by Rohingya refugees.